Clinical impact of neoadjuvant treatment in resectable pancreatic cancer: a systematic review and meta-analysis protocol. Issue 3 (25th March 2016) - Lee, Jong-chan; Ahn, Soyeon; Paik, Kyu-hyun; Kim, Hyoung Woo; Kang, Jingu; Kim, Jaihwan; Hwang, Jin-Hyeok
Abstract : Introduction: Although the only curative strategy for pancreatic cancer is surgical resection, up to 85% of patients relapse after surgery. The efficacy of neoadjuvant treatment in resectable pancreatic cancer (RPC) remains unclear and there is no systematic review focusing fully on this issue. Recently, two prospective trials of neoadjuvant treatment in RPC were terminated early because of slow recruiting and existing randomised controlled trials (RCTs) have too small sample sizes. Therefore, to overcome probable biases, it would be more reasonable to include both RCTs and non-randomised studies (NRSs) with selected criteria. This review aims to investigate the effect of neoadjuvant chemotherapy (CTx) and chemoradiation therapy (CRT) in RPC using RCTs and specific NRSs. Method and analysis: This systematic review will include conventional RCTs as group I, and quasi-randomised controlled trials, non-randomised controlled trials and prospective cohort studies as group II. Two groups will be assessed and analysed separately. Comprehensive literature search will use Medline, Embase, Cochrane library and Scopus databases. Additionally, we will search references from relevant studies and abstracts from major conferences. Two authors will independently identify, screen, include studies, extract data and assess the risk of bias. Discrepancies will be resolved by consensus with another author. An independent methodologist will categorise and assess NRSs to minimise heterogeneity. In each study group, meta-analysis will be conducted using a random-effect model and statistical heterogeneity will be evaluated using I 2 -statistics. Publication bias will be visualised with contour-enhanced funnel plots and analysed with Egger's test. In group I, cumulative meta-analysis will be considered because the CTx regimen and CRT protocol have changed. The quality of evidence will be summarised using the GRADE (Grading of Recommendations Assessment, Development and Evaluation) approach. Ethics and dissemination: This review does not use primary data, and formal ethical approval is not required. Findings will be disseminated through peer-reviewed journals and committee conferences. Trial registration number: CRD42015023820.